FEATURES OF STUDYING BI-SYSTEMS BY STUDENTS OF ECONOMIC SPECIALTIES ON THE EXAMPLE OF THE FINANCIAL MODEL OF THE UNIVERSITY - Vinnik, Maksym; Poltorackiy, Maksym; Konnova, Olha (Journal of Information Technologies in Education (ITE), 2021)
Modern higher education should enable graduates to be in demand and competitive on the labor market. It is important for students to acquire knowledge and skills that meet the needs and requirements of employers. We have analyzed a large number of vacancies on one of the largest job search platforms in Ukraine – Work.UA and found out that an important requirement for candidates for the positions of data analyst and business analyst is the ability to work with BI tools. In this paper, we looked at the most popular BI systems, namely Power BI, Tableau, QlikView, Qlik Sense, Looker and Google Data Studio. Based on the analysis, we came to the conclusion that Power BI is one of the most effective systems of this type. It should also be noted that this tool is popular among employers: a large number of vacancies require knowledge and experience with this system. Therefore, in our opinion, Power BI is the best tool for students to study economics. In addition, it should be emphasized that Power BI provides quite rich free functionality that allows users to effectively work with data. In this work, we give an example of using the Power BI system in the preparation of students of economic specialties. We consider the process of using this tool for the development of visual reports on the example of the financial model of the university. This approach simplifies the process of analyzing data and allows for more flexible access to them. Studying BI systems allows you to more effectively train specialists in data analysis and business analytics. It enables students to receive modern and relevant knowledge in this area.